Pemanfaatan Lampu Panel Surya untuk Penerangan Jalan Lingkungan - Bagus Soebandono; Anita rahmawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Solar street lighting (PJU) is an innovation of Appropriate Technology (TTG) as a result of energy engineering from the heat of solar light (the sun) which is converted into electrical energy, stored in batteries and used as a power source for streetlamp lighting. The main reliability of the solar led PJU is that it is not affected when the PLN electricity distribution network is in trouble or maintenance, because the solar led PJU can meet its own energy needs and not from the PLN electricity network. Environmental street lighting in the Minggir III area, RT.01/RW. 06 Sendangagung, Minggir, Sleman is not widely available, so it can interfere with the comfort and safety of road users at night. The livelihoods of the people in this area are farming, raising livestock and trading which often have to be active at night. With this public street lighting, it is hoped that it can provide comfort for road users and the surrounding environment.